2020
DOI: 10.1107/s2053229620010803
|View full text |Cite
|
Sign up to set email alerts
|

4-Styrylquinolines from cyclocondensation reactions between (2-aminophenyl)chalcones and 1,3-diketones: crystal structures and regiochemistry

Abstract: Structures are reported for two matched sets of substituted 4-styrylquinolines which were prepared by the formation of the heterocyclic ring in cyclocondensation reactions between 1-(2-aminophenyl)-3-arylprop-2-en-1-ones with 1,3-dicarbonyl compounds. (E)-3-Acetyl-4-[2-(4-methoxyphenyl)ethenyl]-2-methylquinoline, C21H19NO2, (I), (E)-3-acetyl-4-[2-(4-bromophenyl)ethenyl]-2-methylquinoline, C20H16BrNO, (II), and (E)-3-acetyl-2-methyl-4-{2-[4-(trifluoromethyl)phenyl]ethenyl}quinoline, C21H16F3NO, (III), are isomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…1-3). These new 2-methylquinoline derivatives (I)-(III) are intended for use as key precursors in the further development of more complex molecules of possible biological value, such as the bis-styrylquinolines (IV) (Scheme 2), (4-styrylquinolin-2-yl)chalcones of the type (V), and the molecular hybrids of types (VI) and (VII), and the work reported here can be regarded as a continuation of an earlier crystallographic study which reported the structures of 2-methyl-4-styrylquinolines having either acetyl or carboethoxy functionalities at position C3 (Rodrı ´guez et al, 2020).…”
Section: Resultssupporting
confidence: 63%
“…1-3). These new 2-methylquinoline derivatives (I)-(III) are intended for use as key precursors in the further development of more complex molecules of possible biological value, such as the bis-styrylquinolines (IV) (Scheme 2), (4-styrylquinolin-2-yl)chalcones of the type (V), and the molecular hybrids of types (VI) and (VII), and the work reported here can be regarded as a continuation of an earlier crystallographic study which reported the structures of 2-methyl-4-styrylquinolines having either acetyl or carboethoxy functionalities at position C3 (Rodrı ´guez et al, 2020).…”
Section: Resultssupporting
confidence: 63%
“…The 4-styrylquinoline precursors of type (I) (see Scheme 1) were prepared using a previously reported method (Mele ´ndez et al, 2020;Rodrı ´guez et al, 2020). In the NMR data listed below, for compounds (III), unprimed ring atoms form part of the quinoline unit, ring atoms carrying a single prime form part of the benzimidazole unit and ring atoms carrying a double prime form part of the styryl unit (see Figs.…”
Section: Synthesis and Crystallizationmentioning
confidence: 99%
“…The work reported here can be regarded as a continuation of an earlier crystallographic study which reported the structures of 4-styrylquinolines having different substituents at the C2 and C3 positions (Rodrı ´guez et al, 2020;Vera et al, 2022;Ardila et al, 2022).…”
Section: Introductionmentioning
confidence: 56%